PENGAWASAN KANTOR IMIGRASI KELAS 1 PEKANBARU TERHADAP WARGA NEGARA ASING PEMEGANG IZIN TINGGAL TERBATAS (ITAS) DI KOTA PEKANBARU TAHUN 2017 - Dimas Triwinaldi; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Immigration Supervision is a series of activities carried out to collect, process and present immigration data and information on Indonesian citizens and foreigners in order to ensure compliance with the provisions of legislation in the field of immigration. Office. As a potential area for foreigners to enter, the city of Pekanbaru through its class 1 immigration office acts as a licensee and also oversees a Limited Stay Permit (ITAS) owned by foreign nationals. In Pekanbaru, immigration violations were discovered by foreign nationals, holders of limited residence permit cards have exceeded the time limit of residence or are known as overstay, and misuse of residence permits leading to forced repatriation or deportation to their home country.   The formulation of the problem in this study are: 1) How is the supervision of the Class 1 Immigration Office Pekanbaru against foreign nationals holding limited residence permits (ITAS) in Pekanbaru City in 2017 ?; 2) What are the inhibiting factors for the supervision of the Class 1 Pekanbaru Immigration Office against foreign citizens holding limited residence permit (ITAS) in Pekanbaru City in 2017 ?. This study aims to: 1) Know the supervision of Pekanbaru Class 1 Immigration Office against foreign nationals holding Limited Stay Permits (ITAS) in Pekanbaru City in 2017; 2) To find out the inhibiting factors for the supervision of the Immigration Office Class 1 Pekanbaru against foreign citizens holding limited residence permits (ITAS) in Pekanbaru City in 2017. Based on the results of the study, the supervision carried out by the Pekanbaru Class 1 Immigration Office against foreign nationals holding the ITAS in Pekanbaru has gone quite well, although there are still some inhibiting factors. The following are the findings of the author: 1) Setting standards in granting licenses and supervision of foreigners in Pekanbaru is in accordance with established regulations; 2) Measures regarding the standards set by Pekanbaru immigration are good, but the implementation of field supervision is only based on reports from the community; 3) The corrective actions taken by Pekanbaru immigration are in accordance with the regulations. There are inhibiting factors for the supervision of the Class 1 Immigration Inspiration Office against foreign nationals of ITAS holders: 1) Lack of human resources, 2) Lack of budget, and 3) Lack of facilities (facilities and infrastructure). Keywords: Supervision, Immigration, ITAS